Antibody Response following Exposure to SARS-CoV-2: Is It a Reliable Marker of Immunity? - Mona Dhakal; Om Prakash Dhakal; Dhurba Bhandari (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Infection and vaccination with the viral vector vaccine Covishield are both expected to produce immunity in the body against Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Production of neutralising antibodies as a result of the humoral immune response plays a key role in defending against this deadly infection. A lack of virus-specific antibodies in the serum does not always imply a lack of immunological memory. The immune response mediated by T cells is also important. Aim: To check for the humoral immune response after exposure to the SARS-CoV-2 virus. Materials and Methods: This cross-sectional observational study was carried out at Central Referral Hospital (CRH), a tertiary care hospital in Gangtok, Sikkim, India, from May to June 2021. A total of 90 participants were divided into three equal groups; unvaccinated with a history of infection with SARS-CoV-2 in the recent past, vaccinated but no infection and history of vaccination and infection both, respectively. The test was performed with COVISCREEN. It’s a double antigen sandwich immunoassay that can detect total antibodies (IgM+IgG+IgA) simultaneously to the SARS-CoV-2 virus. The Statistical Package for the Social Sciences (SPSS), version 16.0 for Windows, was used to analyse the data. Results: Overall, 30 (33.3%) participants showed positive antibody tests out of total 90. Participants with prior infection exhibited more antibody responses irrespective of the vaccination status as compared to vaccinated participants with no prior infection, this difference was statistically insignificant (p=0.165). Conclusion: Both B cell, as well as T cell immune responses following infection and vaccination, need to be evaluated to predict long term immunological memory and protective immunity against future infections with SARS-CoV-2.